PROFIL ADVERSE DRUG REACTION OBAT ANTIDIABETES PADA PASIEN PROLANIS DI PUSKESMAS PAGIYANTEN KECAMATAN ADIWERNA - Auranisa, Wiwit Baitul (Journal Pharmactive, 2025)
The use of antidiabetic drugs often results in side effects experienced by patients with type 2 diabetes mellitus, such as dizziness, nausea, tingling sensations, weakness, hypoglycemia, and gastrointestinal disturbances. These side effects commonly occur in patients undergoing long-term therapy. The relationship between drug side effects and drug use can be assessed using the Naranjo algorithm. At Puskesmas Pagiyanten, Prolanis patients are treated under a program implemented by the government in collaboration with BPJS Kesehatan. Indonesia ranks as the fifth country with the highest number of diabetes patients globally, with 19.5 million cases reported in 2021. Puskesmas Pagiyanten recorded 1,046 cases of diabetes mellitus in 2023, which increased to 1,098 cases in 2024. This study aimed to determine the prevalence, types, and probability scores of antidiabetic drug side effects in Prolanis patients with type 2 diabetes mellitus at Puskesmas Pagiyanten, Adiwerna Subdistrict. This research was an observational study with a cross-sectional design, involving 40 Prolanis patients as the sample using total sampling. Data sources included primary data obtained through direct interviews with Prolanis patients and secondary data from medical records. The results showed that the highest prevalence of side effects was found in Metformin users (63%), followed by the combination of Metformin and Glimepiride (38%). According to the Naranjo algorithm, 57.50% of the side effects were categorized as probable, indicating a high likelihood of being related to drug use. Thus, regular monitoring of drug side effects is necessary to improve the safety of long-term therapy in type 2 diabetes mellitus patients.